Finite Element Modelling of Reinforced Concrete Beam Strengthened with Embedded Steel Reinforcement Bars - Nurman Chandra; Ridwan Ridwan; Muhammad Ikhsan (Journal of Applied Materials and Technology, 2019)
The increased of loads on existing reinforced concrete infrastructure and the lack of initial design and construction will induce flexural and shear failure. Several methods have been introduced to increase the shear capacity of existing reinforced concrete elements with FRP, involving the use of plates or fabric externally bonded (EB) to the webs of the bridge beams, prestressed straps wrapped around the beams or bars mounted within grooves prepared in the near-surface mounted (NSM) technique. Typical Indonesian concrete bridges consisted main girders connected with diaphragm beams where the distance between those girders are very close. In particular case, where the webs of the beams are difficult to access, a novel approach is introduced, namely deep embedment (DE) method. Three reinforced concrete beam models are prepared for this study. One specimen is the control specimen and identified, as Beam-CS and the other two are the strengthened specimens and identified as Beam-SS-3EB and Beam-SS-5EB. All specimens have the same dimensions and reinforcement configuration. Specimen Beam-SS-3EB was strengthened with three rows of 6 mm embedded plain steel bars while specimen Beam-SS-5EB was strengthened with five rows of 6 mm plain steel bars. The results showed that element size significantly affects the load-displacement curve behaviour. The similarity of the hysteresis curve in the FE analysis using the 25 mm element size suggested a reasonably good agreement between the analytical calculation and the prediction result from the FE analysis. Furthermore, maximum reaction force for Beam-SS-3EB and Beam-SS-5EB were 30.30 kN and 31.77 kN, respectively, represents an increase of 17.67% and 23.29% compared to that of the Beam-CS.